Clinical Outcomes of Autologous Hematopoietic Stem Cell Transplant in Multiple Myeloma Patients: A 5-year Experience from a Single Centre in North India - Sood, Nitin; Tiwari, Aseem Kumar; Pabbi, Swati; Dikshit, Roshan; Singh, Prerna; Ramaswami, Amrita; Gautam, Dheeraj; Singh, Manish Kumar (South Asian Journal of Cancer, 2022)
Introduction Multiple myeloma (MM) forms a significant proportion of hematological malignancies. Autologous transplantation continues to be an effective consolidation strategy in resource-restricted settings such as India.Objectives The main objective of the study was to analyze the clinical outcomes of autologous hematopoietic stem cell transplant (HSCT) in MM patients in a single tertiary care center in north India over a period of 5 years.Materials and Methods This retrospective observational study was conducted in a tertiary care center in north India. Data of all MM patients who underwent HSCT between January 2014, and December 2018, were analyzed. The outcome of HSCT was investigated in terms of transplant-related mortality (TRM), progression-free survival (PFS), overall survival (OS), and relapse. PFS and OS were calculated by Kaplan–Meier method and differences between the groups were tested for statistical significance using the two-tailed log-rank test. Life-table method was used for the estimation of survival rate at 1, 3, 5, and 6 years.Results Patient characteristics and survival post-transplant was similar to other published Indian studies. In total, 378 patients were diagnosed with MM in our hospital between 2014 and 2018. One hundred ninety-three patients were found to be eligible for autologous HSCT, out of which 52 ended up having a transplant giving us a high percentage (26.9%) of patients receiving a transplant in our setting. Transplant-related mortality (TRM) was nil in the present study. The mean PFS and OS were 62.8 and 70.1 months, respectively. The mean PFS and OS rates at 5 years were 75.3% and 84.2%, respectively. The average cost estimate of HSCT in our setting was 7.2 lakh Indian national rupees.Conclusion Autologous HSCT is a safe procedure with nil 100-day mortality in present series. Moreover, considering the cost of novel agents, autologous transplant remains a cost-effective way for prolonging remission and time-to-next treatment in India.
Keywords: myeloma; multiple myeloma; autologous transplant; hematopoietic stem cell transplant